Natural lighting as a factor in performance industrial environments - Garlet, Eliane; Dos Santos, Lucas Almeida; Perufo, Larissa Disconzi; Godoy, Leoni Pentiado; Marzall, Lucina Fighera (Revista de Administração da UFSM, 2015)
The search for new alternatives that maximize its performance in the economic market have led many companies to invest high values on technological products that enable them to reduce costs, increase profitability and make increasingly effective performance of its employees in production processes. This exploratory paper, which will use a literature based on relevant literature to structure the proposed theme, also characterized as a case study in a large company of the mechanic metal sector, aims to analyze the usage implement a system of natural lighting, integrated with artificial lighting system in their plants, specifically in Hall A. As main results, we could verify the advantages that can be provided with adequate lighting, improving the productivity of its employees, in addition to reducing costs while operating the company to sustainably use the artificial lighting linked to natural lighting, as well as reducing future health problems of employees.